(untitled) (Res Gesta, 2018)
Wars are ubiquitous around the globe. However, they have not been the focus of intense study in the social sciences. Especially sociology has not paid much attention to war as an object of study since its development as a science. We should not forget the incidence war has in the development of daily life, which has been hitherto ignored. Since 1868 Cuba’s Independence War showed in its development a wide array of strategies. Distinct social sciences have advanced our scientific knowledge of it. But in this particular case, we pretend to explain, from the perspective of the sociology of war and conflict, the Cuban case from several points of view (e. g., ranging from its asymmetric and diffuse nature to its representations).